2009
DOI: 10.1148/radiol.2511081286
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Pancreatic Cystic Neoplasms from Pancreatic Pseudocysts at MR Imaging: Value of Perceived Internal Debris

Abstract: Presence of internal dependent debris appears to be a highly specific MR finding for the diagnosis of pancreatic pseudocyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 15 publications
0
26
0
5
Order By: Relevance
“…It is important to look for this characteristic because it is highly specific to pseudocysts. Macari et al [55] reported that on MRI, 13 of 14 (93%) pseudocysts had debris but only 1 (4%) of 22 cystic neoplasms had debris. Debris is very easily seen with EUS.…”
Section: Eus In Cystic Lesionsmentioning
confidence: 99%
“…It is important to look for this characteristic because it is highly specific to pseudocysts. Macari et al [55] reported that on MRI, 13 of 14 (93%) pseudocysts had debris but only 1 (4%) of 22 cystic neoplasms had debris. Debris is very easily seen with EUS.…”
Section: Eus In Cystic Lesionsmentioning
confidence: 99%
“…Large pancreatic pseudocysts can cause local mass effect. (9) They can also be complicated by secondary infection, bleeding and rupture; secondary infection is associated with a high rate of morbidity and mortality, and thus requires emergent drainage.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the morphological features of cystic lesions are not sufficient for arriving at a conclusive diagnosis, further characteristics have to be evaluated such as evidence of a solid component, infiltrating tumor growth exceeding the organ borders or pancreatic ductal obstruction. Debris in combination with a history of pancreatitis is indicative of pseudocysts [14,15]. …”
Section: Characterization Of Pancreatic Massesmentioning
confidence: 99%